Interprofessional Education with Simulations in Primary Care - KLEMENC-KETIŠ Zalika; ZAFOŠNIK Uroš (Sciendo, 2024)
The introduction of interprofessional primary care (IPC) as a model of collaborative patient care is increasingly vital in the context of complex healthcare systems and the growing needs of patients. Its benefits include improved patient outcomes, enhanced efficiency, and reduced costs. However, the successful implementation of IPC faces challenges due to the differences in training and backgrounds among healthcare professionals, emphasising the importance of effective teamwork and collaborative education.